The Concept of Education Based on the Term Al-Hikmah in the Qur'an and Its Relevance in Forming the Religious Character of Students - Idhar Idhar (Prodi PAI STIT Sunan Giri Bima, 2026)
The moral crisis, character degradation, and rapid technological advancement require Islamic education to move beyond the mere transmission of knowledge toward the cultivation of students' religious character based on Qur'anic values. One of the fundamental concepts underpinning Islamic education is al-hikmah (wisdom), which encompasses profound knowledge, sound judgment, and the proper application of knowledge in everyday life. This study aims to examine the educational concept of al-hikmah in the Qur'an and explore its relevance to the formation of students' religious character through an analysis of Qur'an Surah Al-Baqarah (2:269), An-Nisa' (4:113), Al-Ma'idah (5:110), and Luqman (31:12). This qualitative study employed a library research design using a semi-thematic (semi-maudhu'i) Qur'anic exegesis approach and content analysis of the selected verses, supported by classical and contemporary tafsir literature as well as relevant Islamic education studies. The findings reveal that al-hikmah represents a holistic paradigm of Islamic education integrating spiritual, intellectual, moral, and social dimensions through the balance of knowledge, faith, righteous action, and noble character. Each Qur'anic verse contributes complementary educational principles, including wisdom in applying knowledge, awareness that knowledge is a divine gift, the integration of beneficial competencies, and the cultivation of gratitude and moral integrity. This study concludes that al-hikmah-based education provides a comprehensive conceptual framework for strengthening students' religious character and contributes to the development of a more holistic paradigm of Islamic education.